تجلیات اللغة الایحائیة في دعاء الصباح للامام علي بن ابي طالب (علیھ السلام) (Journal of the College of Education for Women, 2019)
The literary aspect of any text reveals when it used The inspiration languagewhich reveals the creative aspect of language for the creator (writer) he in turnwill seek for the best choice from these aspects then, he will distribute them dueto their intention, and according to the their contextThus, propagandistic text contains many moral features which the languageaccord to thus , we found that the morning (dua al asbah)is full of creativeliterary manifestations through many abstentions which happened in differentstructures that contain the text, especially in structure of metaphor, and contrast.we found many outstanding gaps and abstentions in these are given life, matterthat gives the text the most literary featuresIn the contrast structure, it works apparently to observe differences betweenthings, but in its depth, the familiarity and integration appear between differences.In the constructive structure ,the abstention appears through prayingstructure ,which refrain from imperative structure because it consist the requestfrom the lower to the upper though the imperative structure, originally containsthe request from the upper to the lower. the interrogative structure has deviatedfrom its ordinary context which mean asking for some thing unknown, and theinterrogative appears in the praying text has refrained from determination.The rhymed prose structure appears as giving the required rhythm for thetext and supports with vocal in aspiration ,the rhymed prose is intensively usedwhich made the text reflected the approached meanings.